Popper, Bouvard y Pécuchet. Nueva refutación del Mundo - Henríquez Garrido, Ruy J. (Logos. Anales del Seminario de Metafísica, 2002)
Using the plot of Flaubert’s novel Bouvard and Pécuchet, as a possible refutation of Popper’s World 3, we have analyzed some of the main consequences on the Philosophy of Mind, as well as for Science and Knowledge, that Popperians’ thought has over the so called world of the objective knowledge.